Pemanfaatan Limbah Cangkang Kerang Lokan (Geloina Expansa) Sebagai Biokoagulan Untuk Menurunkan Fosfat Pada Limbah Cair Laundry - Davidson Davidson; Syarfi Daud; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Availability of Lokan calm shells waste (Geloina Expansa) has great potential to be used as raw material of chitosan biocoagulant. Chitosan has bioactivity properties, biodegradability, no hazardous materials and have oxygen binding force in the waste water, and it is very potential to be used as an environmentally friendly biocoagulant in the wastewater treatment process. High concentrations of detergent in water is coming from the laundry activities and it can caused decrease water quality and environmental pollution like increased levels of phosphate, because of that the preliminary treatment is needed by using coagulation-flocculation method. The research process was done gradually starting from extraction lokan calm shells to chitosan by deproteination process, demineralization and deacetylation, followed by coagulation-flocculation method. The variation of this study are dose of coagulant by 225 mg/l, 250 mg/l, 275 mg/l and 300 mg/l. The phosphate parameters was analyzed in laboratory referring to SNI 06-6989.31-2005. Based on the laboratory results, it showed that the maximum allowance of phosphate parameters were 80.71% respectively at 250 mg/l coagulant dose. From this research chitosan is able to removal phosphate parameters in laundry wastewater so that the results was obtained accordingly with some parameters PERMENLH/5/2014.Keywords: Laundry, Chitosan, phosphate, coagulation-flocculation